A High-Quality Genome Assembly of Sorghum dochna - Chen, Yu; Zhang, Yongbai; Wang, Hongjie; Sun, Juan; Ma, Lichao; Miao, Fuhong; Zhang, Zixin; Cheng, Yang; Huang, Jianwei; Yang, Guofeng; Wang, Zengyu (Frontiers in Genetics, 2022)
S. dochna is a high-quality bio-energy crop that also serves as human and animal food. However, information on its genomic characteristics is scanty. In this study, we presented a high quality assembly of S.dochna with PacBio long read, Illumina short read, Hi-C sequencing data, gene annotation, and comparative genome analysis. The results showed that the genome size of S. dochna was assembled to 777Mb, with contigN50 of 553.5Kb and GC content of 43.90%. Besides, gene annitation predicted 37,971 genes and 39,937 transcripts in S.dochna genome. A total of 7,899 S. dochna genomic annotations was annotated in six databases. Cafe software analysis showed that 191 gene families were significantly expanded, while 3,794 were significantly contracted in S. dochna. The high-quality genome map constructed in this study provides a biological basis for future analysis of the biological characteristics of S. dochna, which is crucial for its breeding.